TALAK DAN IDDAH DALAM PERSPEKTIF AL-QUR'AN DAN HADIS - Hasanudin Hasanudin (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2021)
Divorce and iddah as the two parts described in Islam, of course, have obtained legality by syara '. The basis for the legal requirements for divorce and iddah is contained in the Koran and Sunnah, and has been agreed upon by the Ulama in the form of ijma 'on its legality. Divorce is a narrow